Dipeptide Conjugates: An Important Class of Therapeutic Agents - Borse, Ankita; Shinde, Nirmala; Bhosale, Sachin Kawaduji (Indian Journal of Pharmaceutical Education and Research, 2023)
Dipeptide conjugates and conjugates of amino acids with heterocycles or other chemical entity are significant class of medicinal compounds with a wide range of biological actions including antibacterial, antiviral, anticancer, antimalarial, and immunomodulatory activity. Such conjugates demonstrated a wide range of applications in biology and are utilized in a number of fields including medicinal chemistry, material science etc. The several biological activities shown by these conjugates are encouraging the chemists and researchers in this field to synthesize and screen them for various biological activities. This review highlights the research work carried out in this area in relation to the synthesis of conjugates for various biological activities.
Keywords: Anticancer; Immunoactivators; Antivirals; Antimicrobials; Antimalarials